Brezstropa jama v Podbojevem lazu, Rakov Škocjan - Stepišnik, Uroš (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2009)
This paper presents a denuded cave situated in the area of Podbojev laz, on the northwestern side of the Rakov Škocjan. Morphometric and morphogenetic properties of several sections of the denuded cave and its surroundings are described in detail. The denuded cave developed from an epiphreatic cave system which used to function as an outflow cave system from the Rak valley. Morphometrical analysis of the slopes show that the denuded cave was developedin stages. As the surrounding surface is not flattened, the cave roofmust have been denuded gradually.
Keywords: krasoslovje; kraške jame; List of caves in Slovenia; Rakov Škocjan; Rakov Škocjan, Cerknica